(untitled) (Biological Sciences - PJSIR, 2003)
Desulphurization of lignitic coal of Pakistan, using an aqueous solution of cupric ions as an oxidant at different temperatures was accomplished in sealed tubes. Desulphurization occured as reaction started. At the early stage of reaction, reduction of sulfur was rapid and thus with the passage of time it became slow. Increment in the level of desulphurization occurred with the increasing concentration of cupric ions and temperature. Reduction of sulfur drops of the levels of ash contents and enhances the value of Clorific Value (CV) .